Humorous Discourse on Indonesian Students™ Protest Slogans - Tasya, Vivi Dwi; Saragih, Amrin (TRANSFORM: Journal of English Language Teaching and Learning, 2021)
The objectives of this study were to find out what, how, and why humor were realized on Indonesian students™ protest slogans. The method of this research is descriptive qualitative. The data was taken from all the words, phrases, clauses, sentences written  in Indonesian students™ protest slogans. The result shows that there are two types of humor found in Indonesian students™ protest slogans, namely collective identities with total number 7 slogans (35%), the effect of participation with total number 6 slogans (30%), frames with total number 5 slogans (25%) and tactics with total number 2 slogans (10%). Collective identities showed that K-Popers, gamers, introverts are not only as community but also as a new power to strengthen a sense of ˜we™ in social movement. Humor also has the effect of participation on enhancing engagement and preventing burnout by including their personal life experience intentionally and explicitly. Indonesian students™ protest slogans showed frames by using some symbols and some analogies to the popularity (music, drama, song title) to attact public  interest and the protesters brought or wear some attribute in the movement to establish a repertoire and interpreted as an action to get their message across. There were two dualistic reason of using humor in the societal level. Collective identities as the emphasis on differentiation reflects a strong identification to make it possible to exclude the others, while the effect of participation, frames and tactics act as control or resistance which mean a form of attack and challenge the power and become a new way for communicating among the protesters and to establish a new relationship with the power.